Synergistic Effect of Bioactive Anticarcinogens from Soybean on Anti-Proliferative Activity in MDA-MB-231 and MCF-7 Human Breast Cancer Cells In Vitro - Yingying Zhu; Yang Yao; Zhenxing Shi; Nadia Everaert; Guixing Ren (Molecules, 2018)
Consumption of soybean products has been implicated in the prevention of breast cancer. This study provides insights into the anti-proliferative activity of 12 anticarcinogens from soybean by single or two-way combination treatment against MCF-7 and MDA-MB-231 human breast cancer cells. Results showed that genistein, daidzein, glycitein, genistin and dainzin showed stronger anti-proliferative activity against MCF-7 cells with EC50 values of 66.98 ± 4.87 μM, 130.14 ± 2.10 μM, 190.67 ± 5.65 μM, 72.82 ± 2.66 μM and 179.21 ± 6.37 μM, respectively. There is a synergistic effect of combination treatment of genistin plus daidzin in MCF-7 cells with combination index at inhibition of 50% (CI50) of 0.89 ± 0.12. Genistein, glycitein, genistin and β-sitosterol were demonstrated to have a stronger anti-proliferative activity against MDA-MB-231 cells with EC50 values of 93.75 ± 5.15 μM, 142.67 ± 5.88 μM, 127.82 ± 4.70 μM and 196.28 ± 4.45 μM. The synergistic effect was observed in the mixture of genistein plus genistin, genistein plus β-sitosterol or β-sitosterol plus genistin with CI50 values of 0.56 ± 0.13, 0.54 ± 0.20 and 0.45 ± 0.12, respectively. These bioactive anticarcinogens were able to inhibit invasion and migration of breast cancer cells and the combination treatments enhanced the inhibitory effect. Regulation of PI3K/Akt/mTORpathway seems to be the main mechanisms involved in the anticancer activity.